2007
DOI: 10.1111/j.1479-8425.2007.00316.x
|View full text |Cite
|
Sign up to set email alerts
|

The quality of sleep and factors associated with poor sleep in Japanese graduate students

Abstract: We conducted a cross-sectional mail questionnaire survey at 31 graduate schools on 12 university campuses in Kyoto, Japan to assess the sleep quality of the graduate students and to describe the factors associated with their poor sleep quality. A total of 241 responses were returned (44%) and we analyzed the data of 219 graduate students (158 men and 61 women, aged 22-39 years). The participants completed the self-reported Pittsburgh sleep quality index (PSQI) questionnaire, together with socio-demographic, ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
6

Year Published

2012
2012
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 25 publications
0
26
0
6
Order By: Relevance
“…College students in Ethiopia, and possibly other parts of East Africa, should be made aware of the impact of caffeine beverage consumption and khat use on sleep quality and patterns. Improved sleep quality benefits college students in their daily activities, academic performance, and also improves their health status [22, 30, 41, 42]. A technology-filled and fast-paced society may be the reason many college students overlook the significance of adequate sleep.…”
Section: Discussionmentioning
confidence: 99%
“…College students in Ethiopia, and possibly other parts of East Africa, should be made aware of the impact of caffeine beverage consumption and khat use on sleep quality and patterns. Improved sleep quality benefits college students in their daily activities, academic performance, and also improves their health status [22, 30, 41, 42]. A technology-filled and fast-paced society may be the reason many college students overlook the significance of adequate sleep.…”
Section: Discussionmentioning
confidence: 99%
“…In a survey study of 219 Japanese graduate students, 25.6% of the students were identified as poor sleepers and poor sleep quality was related to poor perceived health (Palios, Gergely, Yamada, Miyazaki, & Okawa, 2007). The negative impact of sleep deprivation and fatigue was noted in a study that found that first-and second-year medical residents who reported sleeping five hours or less per night were more likely to report serious accidents or injuries, confiict with other professional staff, and having made significant medical errors (Baldwin, & Daugherty, 2004).…”
Section: Sleep and Stressmentioning
confidence: 99%
“…College students experience a number of sleep problems 6,7 and should learn the importance of healthy sleep 8 . A good quality of sleep is essential to enable university students to comprehend, analyze, and absorb enormous amounts of information during the study process 8,9 .…”
Section: Introductionmentioning
confidence: 99%